Leptin levels in patients with Parkinson's disease: A systematic review and meta-analysis. (February 2021) - Rahnemayan, Sama; Mirghafourvand, Mojgan; Fathalizadeh, Arezoo; Faramarzi, Elnaz; Reyhanifard, Anita; Mahmoodpoor, Ata; Sanaie, Sarvin
Summary: Background and aims: The exact mechanism of Parkinson's disease (PD) is not fully understood yet, but it is suggested that inflammation is one of its contributing factors. Among several inflammatory factors, adipokines, especially leptin may have a great role in this mechanism; since it is not only causing inflammation, but it can also play other roles in the body that may contribute to the symptoms described for PD. Regarding the contradictions in the association of serum leptin levels with Parkinson's disease, a systematic review and meta-analysis was performed to have a more accurate estimation of this relationship. Methods: Published literature was obtained by searching PubMed, Embase, Cochrane Library, Scopus, Ovid, ProQuest and Google Scholar. Random-effect model analysis was used to calculate pooled standard mean difference (SMD) with 95% confidence interval (CI). Heterogeneity was tested with the heterogeneity statistic Q and quantified using I 2 . Newcastle-Ottawa scale was used to assess the study quality. Results: Six studies including a total number of 198 PD patients and 182 controls were finally included in the meta-analysis. Serum leptin levels in PD patients were non-significantly lower than those in control group (SMD = −0.40 ng/ml, 95% CI -2.33–1.53). Subgroup analyses revealed that serum leptin levels of PD patients and controls in either females or males didn't show any significant difference. Conclusions: This meta-analysis revealed that leptin level doesn't show any significant difference between PD patients and healthy controls, even when taking the participants' gender into consideration.